(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Chemotherapy is still regarded as the major intervention in fighting the malaria scourge despite the recent introduction of malaria vaccine. Screening of medicinal plants provides opportunities for the discovery of the potential drug molecules. Ficus asperifolia (Miq) family Moraceae has been traditionally employed in the treatment of many diseases including pain, fever and malaria. The aim of this study was to examine the anitmalarial activity of both the methanol leaf extract (MEFA) and residual aqueous fraction of Ficus asperifolia (RAF) through the determination of their heme polymerization inhibition ability. The powdered leaf was extracted using 70%